Association of Accelerometer-Measured Physical Activity and Sedentary Time with Epigenetic Markers of Aging. Issue 2 (13th September 2022) - Spartano, Nicole L.; Wang, Ruiqi; Yang, Qiong; Chernofsky, Ariel; Murabito, Joanne M.; Vasan, Ramachandran S.; Levy, Daniel; Beiser, Alexa S.; Seshadri, Sudha
ABSTRACT: Introduction/Purpose: Physical activity may influence chronic disease risk, in part, through epigenetic mechanisms. Previous studies have demonstrated that an acute bout of physical activity can influence DNA methylation status. Few studies have explored the relationship between habitual, accelerometer-measured physical activity or sedentary time with epigenetic markers of aging. Methods: We used linear regression to examine cross-sectional associations of accelerometer-measured physical activity and sedentary time with extrinsic and intrinsic epigenetic age acceleration (EEAA and IEAA) models and GrimAge measured from blood samples from Framingham Heart Study participants with accelerometry and DNA methylation data ( n = 2435; mean age, 54.9 ± 14.3; 46.0% men). Residuals of Hannum-, Horvath-, and GrimAge-predicted epigenetic age were calculated by regressing epigenetic age on chronological age. We took into account blood cell composition for EEAA, IEAA, and AdjGrimAge. Moderate to vigorous physical activity was log-transformed to normalize its distribution. Adjustment models accounted for family structure, age, sex, smoking status, cohort–laboratory indicator, and accelerometer wear time. We additionally explored adjustment for body mass index (BMI). Results: Walking 1500 more steps per day or spending 3 fewer hours sedentary was associated with >10 months lower GrimAge biological age (or 1 month lower AdjGrimAge, after adjusting for blood cells, P < 0.05). Every 5 min·d −1 more moderate to vigorous physical activity was associated with 19–79 d of lower GrimAge (4–23 d lower using EEAA or AdjGrimAge, P < 0.01). Adjusting for BMI attenuated these results, but all statistically significant associations with AdjGrimAge remained. Conclusions: Greater habitual physical activity and lower sedentary time were associated with lower epigenetic age, which was partially explained by BMI. Further research should explore whether changes in physical activity influence methylation status and whether those modifications influence chronic disease risk.